Measuring vulnerability and poverty estimates for rural India - Raghav Gaiha; Katsushi Imai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper measures the vulnerability of households in rural India, based upon the ICRISAT panel survey. We employ both ex ante and ex post measures of vulnerability. The latter are decomposed into aggregate and idiosyncratic risks and poverty components. Our decomposition shows that idiosyncratic risks account for the largest share, followed by poverty and aggregate risks. Despite some degree of risk-sharing, the landless or small farmers are vulnerable to idiosyncratic risks, forcing them to reduce consumption. Income-augmenting policies therefore must be combined with those that not only reduce aggregate and idiosyncratic risks but also build resilience against them.
Keywords: C21; C23; I32; C61; 330; aggregate risks; idiosyncratic risks; poverty; vulnerability; semi-arid conditions; Ländliche Armut; Messung; Indien